OVERCOMING CHALLENGES OF STUDENT ENGAGEMENT IN ONLINE HEALTH PROFESSIONS EDUCATION: AN EXPLORATORY, QUALITATIVE STUDY - Khan, Sana; Khan, Sher Afghan; Khattak, Zainab; Jamil, Brekhna; Ahmed, Sameer; Aitazaz, Fauzia (Pakistan Journal of Physiology, 2024)
Background: Student engagement is a major issue faced in online education. This study aims to explore the challenges of student engagement in online learning for a health professions education program. Methods: This qualitative explorative study was done involving 6 faculty members and 12 students from Pakistan’s three Masters in Health Professions Education (MHPE) programs using semi-structured interviews and NVivo v12.0 for inductive, thematic analysis. Results: The study focused on addressing student engagement challenges and post-pandemic learning preferences, identifying 9 themes including teacher training, internet connectivity, student participation, distraction reduction, online learning environment improvement, and engaging activities. Conclusion: The COVID-19 pandemic has led to a shift to online medical and dental education in Pakistan. However, challenges persist in student engagement. To boost student engagement, medical colleges should implement proper training, high-speed internet and smaller class sizes, requiring administrative efforts and proper infrastructure. Pak J Physiol 2024;20(2):65-9